THE HEDGING IMPACT TO FIRM VALUE OF PUBLIC COMPANIES IN INDONESIA - Arius E.; Achsani N.A.; Bandono B. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
The purpose of this study is to have comprehensive understanding of hedging implementation in the companies which are included in the LQ 45 Index and to comprehend the impact of hedging to the firm value. The data using secondary data which are annual report of public companies that consistently included in the LQ 45 Index on the Indonesian stock exchange for 2015-2018. The sampling technique is purposive sampling method, while the analysis technique is using data panel regression analysis. The finding show that companies which are included in LQ 45 index did hedging actvities to mitigate currency risk that may arise from long-term debt in foreign currencies such as loans with more than 1 year, bonds payable and cash flows. Furthermore, this research did not show that hedging could affect the firm value. Meanwhile, profit and dividend are factor that significantly influence the firm value.